2017
DOI: 10.1007/s13197-016-2469-4
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Himalayan Rhodiola imbricata Edgew. root: a novel source of dietary amino acids, fatty acids and minerals

Abstract: Roots of Edgew from Indian trans-Himalayan cold desert known for their nutritional and medicinal attributes were evaluated for the dietary amino acids, fatty acids and mineral composition. Nine essential and twelve non-essential amino acids were quantified. The contents ranged between 91.33 and 1640.67 µg/g. Histidine (1434.33 µg/g), lysine (1329.33 µg/g) and threonine (1015.67 μg/g) were dominant essential amino acids, while glycine (1640.67 µg/g), proline (1263.67 µg/g), alanine (1142.33 µg/g), cystine HCL (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 33 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have documented that the major bioactive components of Rhodiola include flavonoids, hydrolyzed tannins (namely gallic acid derivatives), phenylpropanoids, amino acids, alkaloids, and organic acids [ 6 , 7 ]. Therefore, changes in these six major categories were subsequently described in detail.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have documented that the major bioactive components of Rhodiola include flavonoids, hydrolyzed tannins (namely gallic acid derivatives), phenylpropanoids, amino acids, alkaloids, and organic acids [ 6 , 7 ]. Therefore, changes in these six major categories were subsequently described in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that Rhodiola contains many phytochemicals, such as flavonoids, phenylpropanoids, tannins, amino acids, alkaloids, organic acids, and volatile oils, etc. [ 5 , 6 , 7 ]. Furthermore, modern research has shown that the comprehensive nourishing effects of the Rhodiola species are largely attributed to its phytochemicals [ 6 ], which exert anti-hypoxic [ 8 ], anti-viral [ 9 ], immune regulatory [ 10 ], anti-tumor [ 11 ], anti-fatigue [ 12 ], anti-depressive [ 2 ], and improvement of learning and memory [ 13 ] effects.…”
Section: Introductionmentioning
confidence: 99%
“…Downshift of oxygen in hypoxic environment has been reported to trigger the synthesis of norleucine in the dominated organism of extreme, stressful ecology 16 . High content of norleucine was also found in Rhodiola imbricata , which dominates the slopes of high altitude peaks 6 . This amino acid, the essential constituent of primitive life could be the marker for evolution of life in hostile atmosphere/extraterrestrial atmosphere and one of the main constituent of S. porticalis among others for high altitude adaptations 16 .…”
Section: Resultsmentioning
confidence: 89%
“…Over the decades, oxidative stress has been recognized as a prime contributing factor in the origin of many diseases. Extensive research points out that ingestion of herbal supplement(s) is linked to a reduced risk of numerous diseases 5 and therapeutic impact of the phytoproducts have been partly assigned to the natural, non-toxic, medicinal as well as antioxidant compounds 1 , 2 , 6 . Being a good source of natural antioxidants, algae are also utilized by medicinal chemists for designing novel pharmaceutical products as a remedy for oxidative stress-induced maladies 2 , 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Essential amino acids have been recognized as nutrient regulators in muscle protein synthesis and tissue regeneration. Therefore, estimation of these nutritional attributes is essential for the development of plant-based foods ( Tayade et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%